Perancangan Data Warehouse Unit Farmasi dan Poliklinik RSUD Siti Fatimah Palembang Menggunakan Metodologi Nine-Step Kimball - Febridiadiraja, Akbar; Rahman, Abdul (Universitas Multi Data Palembang, 2025)
Data warehouse can be used to accommodate and analyze large amounts of data, which can be viewed from various points of view or dimensions. This research aims to help analyze drug data from current activities in the pharmacy unit and polyclinic of RSUD Siti Fatimah Palembang. Because over time data becomes increasingly large, preventing executives from doing all they can to make decisions and impacting the quality of the information itself. Data warehouse can help hospital leaers make better decisions. Observation, interviews, literature research, and star schema design are the research methods used. And the method used for design uses the Nine Step Methodology, which includes 9 stages. These stages include selecting a process, selecting a grain, identifying dimensions, selecting facts, storing initial calculations in a fact table, confirming a dimension table, selecting a database duration, tracking gradual changes in dimensions, determining priorities, and query models. This research shows that the data warehouse can be accessed quickly and precisely, which will help hospitals make decisions. This study found that a histogram-shaped dashboard can help related parties in making decisions at Siti Fatimah Regional Hospital, Palembang.